Teacher Strategies in Teaching Reading Comprehension - Amin, Fakhrurrazi M (English Education : English Journal for Teaching and Learning, 2023)
This research aims at finding out teacher strategy in teaching reading comprehension and students’ respond toward teacher strategy. The study applied qualitative approach. The research instruments were distributed to English tutor and students at Basic English Course (BEC) Langsa. The data were collected through observation, documentation and interview.  The result indicates that there are several strategies applied by English tutor, they are scaffolding strategy, think Aloud strategy and SQ3R. Meanwhile, the students showed positive respond toward teacher strategies in teaching reading comprehension. Then,the students also actively participating during teaching and learning reading comprehension. It can be concluded that the strategies such as scaffolding strategy, think Aloud strategy and SQ3R can be applied in reading to increase students’ comprehension and to create students’ participation.